2016
DOI: 10.4172/2167-0870.1000251
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypocalcemia following Treatment with Denosumab in Patients with Bone Metastases from Prostate Cancer

Abstract: Objective: To evaluate risk factors for Denosumab-induced hypocalcemia in prostate cancer patients with bone metastases. Methods:In this single-arm, open-label, prospective multicenter study, 48 prostate cancer patients with bone metastases received Denosumab (120 mg on day 1) and androgen-deprivation therapy. Serum calcium, albumin, alkaline phosphatase (ALP), and phosphate levels; chronic kidney disease stage; and serum prostate specific antigen and urine N-terminal telopeptide (u-NTx) levels were examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In a recent study, serum alkaline phosphatase was found to be an independent risk factor, especially if the baseline level was greater than 500 IU/l. Likewise, a higher baseline urine N-terminal telopeptide was also found to be correlated independently with the development of hypocalcemia especially when levels were greater than 100 nmol bone collagen equivalents/mmol creatinine [17].…”
Section: Discussionmentioning
confidence: 87%
“…In a recent study, serum alkaline phosphatase was found to be an independent risk factor, especially if the baseline level was greater than 500 IU/l. Likewise, a higher baseline urine N-terminal telopeptide was also found to be correlated independently with the development of hypocalcemia especially when levels were greater than 100 nmol bone collagen equivalents/mmol creatinine [17].…”
Section: Discussionmentioning
confidence: 87%
“…Another risk factor for hypocalcaemia in patients with prostate cancer with bone metastases who received denosumab is high urine-N-terminal telopeptide (u-NTx) levels. Koguchi et al reported that patients who develop hypocalcaemia following treatment with denosumab had a baseline u-NTx of greater than 100 nmol bone collagen equivalents/mmol creatinine 14. In our patient, we did not check u-NTX level.…”
Section: Discussionmentioning
confidence: 61%
“… 10 Incidence of all grade hypocalcemia ( Table 2 ) was higher (14–39.6%) in observational studies. 8 , 12 The symptoms of hypocalcemia can range from non-specific symptoms such as fatigue, hyperirritability to concerning symptoms of tetany such as perioral numbness, paresthesia of hands and feet, muscle spasms, carpopedal spasms, laryngospasm, and focal or generalized seizures. Severe hypocalcemia is relatively rare; however, it can be a severe and life-threatening condition requiring hospitalization and intravenous calcium administration.…”
Section: Discussionmentioning
confidence: 99%
“… 5 7 Chronic kidney disease with low GFR (<30 ml/min/1.73sqm), vitamin D deficiency, low parathyroid hormone level (PTH), hypomagnesemia, extensive osteoblastic metastasis, prior use of bisphosphonates and comorbidities impairing calcium absorption (previous intestinal/bowel surgeries) are known risk factor for hypocalcemia after denosumab use. 8 10 The median half-life of denosumab ranges from 25 to 35 days, and denosumab-induced hypocalcemia usually resolves within 30 days. 11 We present a case of a patient with metastatic prostate cancer with extensive osteoblastic metastasis who developed severe recurrent hypocalcemia after a single dose of denosumab requiring a total of 58 days of high dose intravenous and oral calcium supplementations with three inpatient hospital admissions.…”
Section: Introductionmentioning
confidence: 99%